High-performance thin-layer chromatography fingerprinting, total phenolic and total flavonoid contents and anti-platelet-aggregation activities of Prosopis farcta extracts - Kobarfard, Farzad; Ayatollahi, Seyed Abdulmajid; Khosravi-Dehaghi, Nafiseh; Faizi, Mehrdad; Amidi, Salimeh; Martorell, Miquel; Choudhary, Muhammad Iqbal; Suleria, Hafiz Ansar Rasul; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
Cardiovascular diseases are a leading cause of worldwide death and excessive platelet is closely related with their pathogenesis. Different plants and natural compounds have demonstrated anti-platelet effects. The aim of this study was to report the high-performance thin-layer chromatography (HPTLC) fingerprinting and anti-platelet-aggregation activities of different leaf extracts (n-hexane, chloroform, ethyl acetate, methanol and aqueous) of Prosopis farcta (Syrian mesquite) plant. The results showed a 100% inhibition of aggregation activity after plasmatic adenosine diphosphate (ADP) aggregation activation of ethyl acetate, ethanolic, methanolic and aqueous extracts, at 60 mg/mL concentration. The IC50 ADP value of these extracts ranged between 4.07 and 11.39 mg/mL. Moreover, these extracts reported the highest amounts of phenolic and flavonoid contents. In conclusion, phytochemicals present in P. farcta leaves have anti-platelet-aggregation activities. Future studies are needed to identify the compounds with anti-platelet potential present in P. farcta.